2010
DOI: 10.1158/1078-0432.ccr-10-0581
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Correlation between LINE-1 Hypomethylation and the Malignancy of Gastrointestinal Stromal Tumors

Abstract: Purpose: Gastrointestinal stromal tumors (GIST) are the most important mesenchymal tumors of the gastrointestinal tract. The vast majority of GISTs exhibit activating mutations of KIT or PDGFRA, but epigenetic alteration of GISTs is largely unknown. In this study, we aimed to clarify the involvement of DNA methylation in GIST malignancy.Experimental Design: A total of 106 GIST specimens were studied. Levels of LINE-1 methylation were analyzed using bisulfite pyrosequencing. In addition, methylation of three ot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 45 publications
7
64
1
Order By: Relevance
“…Our data are consistent with previous reports with losses of 1p, 3p, 13q, 14q, 15q, and 22q and gains of chromosomes 4 and 5 (12)(13)(14)(15)(16)(17)(18)(19). Only one previous study of 25 GIST tumors used the same platform and provided comparable high-resolution copy number analysis (17).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data are consistent with previous reports with losses of 1p, 3p, 13q, 14q, 15q, and 22q and gains of chromosomes 4 and 5 (12)(13)(14)(15)(16)(17)(18)(19). Only one previous study of 25 GIST tumors used the same platform and provided comparable high-resolution copy number analysis (17).…”
Section: Discussionsupporting
confidence: 92%
“…Although further molecular mechanisms underlying the development and progression of GIST are not fully understood, they are necessary due to the wide range of clinical behavior. Chromosomal gains and losses resulting in altered gene dosage are known to be recurrent in GIST and believed to have a role in the molecular pathogenesis of these tumors (12)(13)(14)(15)(16)(17)(18)(19). Nevertheless, the target genes remain to be identified within these regions.…”
Section: Introductionmentioning
confidence: 99%
“…To quantify relatively high LINE1 and AluYb8 methylation levels, we used pyrosequencing technology (Igarashi et al 2010). PCR and subsequent pyrosequencing for LINE1 and AluYb8 were performed using the PyroMark kit (Qiagen).…”
Section: Line1 and Aluyb8 Methylation Analysismentioning
confidence: 99%
“…In addition, we recently showed that hypomethylation of repetitive DNA elements is predominantly observed in malignant GISTs, and that global hypomethylation correlates with increased chromosomal aberration (6).…”
Section: Introductionmentioning
confidence: 98%